Protection of Non-Conventional Trademarks: Issues and the Road Ahead - Dr. Komal (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Trademark as discussed under TRIPS agreement are referred to as “any sign, or combination of signs, capable of distinguishing goods or services of one person or entity from those of others”. The major rationale behind the emergence of trademark law is to protect the business, goodwill and reputation associated with the goods and services thereby facilitating the consumers to distinguish between goods or services originating from different sources and eliminating the confusion regarding the origin of the product. Traditionally, a trademark was referred to in its conventional form as any sign, word, slogan or symbol in two-dimensional form which is used to distinguish the products and services of one proprietor from others. In the present time of aggressive marketing, various new techniques are adopted by manufacturers and sellers of goods and services to make their product distinct from those of other potential competitors present in the market and to capture the attention of the consumers. This brought the idea of non-conventional marks in picture. With the change in time, the trademark law is also expanding its horizon from the traditional notion of marks which earlier used to include only two dimensional marks including words, signs, symbols etc. to new form of non-conventional marks such as marks including or originating through color, smell, shape, taste, touch, sound, position and various other forms of non-conventional marks. The use of new forms of marks to distinguish the goods and services from others had also raised several issues for the registration, functioning, distinctiveness and acceptance of these marks as trademark while breaking the old conventionalities. Also, there is an issue related to the non-availability of any uniform standard for the protection of these non-conventional marks. In this research paper, the researchers will look into the various types of non-conventional marks and the various problems pertaining to their registration, graphical representation, working, distinctiveness and absence of uniform standard for protection of non-conventional marks.